Homomorphic Hash and Blockchain Based Authentication Key Exchange Protocol for Strangers - Yao, Hailong; Wang, Caifen; Hai, Bo; Zhu, Shiqiang (2018 Sixth International Conference on Advanced Cloud and Big Data (CBD), 2018)
Modern communication technologies and cryptographic technologies have pushed social networks into the virtual world, but they have also ensured the real existence of social proximity. In the evaluation of social proximity, some decentralized scenarios require the participants bootstrapping tust, and the existing authentication key exchange scheme can hardly satisfy the above requirements. In this study, we have designed a homomorphic hash and Blockchain based authenticated key exchange protocol with privacy protection, and prove its security under the standard model based on hash one-way, discrete logarithm and Blockchain transaction-level security assumption, and discussed the attack that the proposed scheme can resist. Compared with the existing scheme, the proposed scheme does not need the default Unit of Trust, is safer and more flexible, suitable for the scenarios that require strangers to bootstrap trust.